Sport and Fitness in Children and Adolescents A Multidimensional View - Wachira, Lucy-Joy (IntechOpen, 2023)
Participation in fitness and sports activities bestows far-reaching benefits on children's growth, physical and mental development, health, skill acquisition, and physical performance. Besides the typical description of common concepts, subjects, and general literature, this book presents a variety of topics associated with physical activity and fitness among children and youth. Work presented in this book ranges from complex descriptions of the role of vitamin D deficiency on children's physical activity and lifelong health to the analyses of the role of motor proficiency among children with an autism spectrum disorder. Some authors report on the association between physical activity and fitness and cognitive function among children while others describe noted differences in selected physical fitness components among children over a span of 30 years. The book also provides empirical insights into the role and status of school sports. While the feasibility and benefits of designed programmes and organized school activities have been demonstrated, the need for targeted specialized interventions and additional knowledge underpins the need for multidisciplinary and inter-sectoral approaches when working with children.